Surgical Utilization Rates and Timing of Care in a Multidisciplinary Spine Clinic versus a Unidisciplinary Spine Clinic Setting. (16th November 2020) - Benton, Joshua; Weiss, Brandon; Longo, Michael; Ramos, Rafael De la Garza; Gelfand, Yaroslav J; Cezayirli, Phillip C; Castro-Rivas, Erida; Headlam, Mark; Udemba, Adaobi; Williams, Lavinia; Kinon, Merritt D; Girtkind, Andrew; et al.
Abstract: INTRODUCTION: Our institution created a multidisciplinary spine clinic (MSC), combining the expertise of physiatrists, spine surgeons, and pain interventionalists. At the multidisciplinary clinic, a patient is scheduled to see one provider, but that provider can consult other spine specialists during a patient's clinic visit and have the other specialist meet with the patient during the same visit. METHODS: We retrospectively reviewed patients who initially visited a neurosurgeon for spine care at either clinic from July 1, 2018 to June 30, 2019. We collected patient demographics, comorbidities, diagnosed spine pathology, final treatment recommendations (surgery, epidural steroid injections (ESI), physical therapy (PT)), and dates of seeing a treating specialist, receiving a treatment recommendation, and undergoing an intervention. Logistic regression was used to assess if the likelihood for these treatment recommendations differed between USC and MSC when adjusting for potential confounders; Cox proportional hazards regression was used to assess if times to treatment recommendations differed. All analyses were repeated for the propensity score (PS) matched datasets. RESULTS: 850 eligible patients were included: 394 initially seen at the USC and 456 at the MSC. Patients in the USC were more likely to be recommended surgery compared to MSC (22.7% vs. 11.4%, P < . 001) and less likely to be recommended PT (13.4% vs. 23.3%, P < . 001) or ESI (11.6% vs. 17.3%, P = .02). These conclusions still held when controlling potential confounders: USC vs. MSC - Surgery: Odds Ratio [OR] 2.16, 95% CI 1.40-3.35, P < . 001; PT: OR = 0.54, 95% CI 0.36-0.82, P = .004; ESI: OR = 0.62, 95% CI 0.40-0.96, P = .03. Lead times to receiving recommendations for PT were faster at the MSC (Hazard Ration [HR] 0.62, 95% CI 0.44-0.89, P = .009) while recommendations for surgery (HR 1.72, 95% CI 1.20-2.46, P = .003) occurred faster at the USC. Analyses using the PS-matched datasets yielded very similar results. CONCLUSION: Multidisciplinary decision making in an integrated clinic setting can significantly reduce the rates of invasive procedures and also improve lead times to treatment for patients with spinal disorders.